Fish hatchery management (American Fisheries Society, 2001)
Published in North and Central America by the American Fisheries Society. Available exclusively from CABI Publishing in all other territories of the world.Second edition of a leading fish culture manualRelevant for both private and public fish cultureVital as a training tool and as a day to day hatchery resourceThis second edition expands and updates the original Fish Hatchery Management